2011
DOI: 10.1039/c1ce05336a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pentagonal tiling: self-assemblies of pentagonal-shaped macrocycles at liquid/solid interfaces

Abstract: We present a systematic scanning tunneling microscopy study on the 2D self-assembly of pentagonal shaped macrocycles at the liquid/solid interface to gain insight about 2D pentagonal molecular crystallization. Macrocycles with alkyl ester groups form an anti-parallel type linear pattern mainly via favorable intermolecular interactions between the interdigitated alkyl chains at the 1,2,4trichlorobenzene (TCB)/graphite interface. On the other hand, at the TCB/Au(111) interface, they showed a random pattern and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 87 publications
1
28
0
3
Order By: Relevance
“…1 Shape persistence is advantageous for many applications: synthesis of macrocycles, 2 preorganization, 3 in silico design, 4 catalysis, 5 configurationally stable stereochemistry, 6 and hierarchical self-assembly 7,8,9 of multi-functional architectures, 3a,8a,10 To design shape-persistent macrocycles, Moore has suggested that they have limited degrees of conformational freedom, i.e., they are rigid. 11 Yet, through the results obtained in the present study, we were confronted with an apparent contradiction involving cyanostar macrocycles (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…1 Shape persistence is advantageous for many applications: synthesis of macrocycles, 2 preorganization, 3 in silico design, 4 catalysis, 5 configurationally stable stereochemistry, 6 and hierarchical self-assembly 7,8,9 of multi-functional architectures, 3a,8a,10 To design shape-persistent macrocycles, Moore has suggested that they have limited degrees of conformational freedom, i.e., they are rigid. 11 Yet, through the results obtained in the present study, we were confronted with an apparent contradiction involving cyanostar macrocycles (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Perfect tilings would require the fivefold-symmetric shapes to be combined with other shapes, [32] as demonstrated by DĂŒrer, Kepler and Penrose. [33] Self-assembly of fivefold-symmetric shape-persistent macro-cycles has been previously studied at the solid-liquid interface, [34] and pentagonal features were discussed for rubrene and para-terphenyldicyanocerium on noble metal surfaces. [35,36] However, systematic studies of closepacking strategies of pentagonal molecules in the plane have only been addressed with penta-substituted derivatives of corannulene so far.…”
Section: Chiral Reconstruction Of a Metal Surfacementioning
confidence: 99%
“…[345 ] Der gleiche Typ von FĂŒnfeckketten wurde neben anderen Motiven fĂŒr Metall‐organische Netze aus 1,3,5‐Trispyridylbenzol und Kupferatomen auf Au(111)‐OberflĂ€chen gefunden (Abbildung 51 a,b);346 eine Ă€hnliche Struktur wurde auch fĂŒr den fĂŒnfeckigen Makrocyclus 97 auf einer Au(111)‐OberflĂ€che erhalten (Abbildung 51 c). 347…”
Section: Parkettierungsmuster In Anderen Selbstorganisierten Systemenunclassified
“… 2D‐Gitter aus FĂŒnfecken: a,b) FĂŒnfeckketten von 1,3,5‐Trispyridylbenzol 96 mit Cu und346 c) Makrozyklus 97 (R=H) auf einer Au(111)/1‐OctansĂ€ure‐OberflĂ€che,347 d) dichteste FĂŒnfeckpackung in Kristallstrukturen 348. e–i) Muster von 98 auf einer HOPG‐TCB‐OberflĂ€che (HOPG=highly ordered pyrolytic graphite, TCB=1,2,4‐Trichlorbenzol) 350.…”
Section: Parkettierungsmuster In Anderen Selbstorganisierten Systemenunclassified
See 1 more Smart Citation